2010
DOI: 10.1348/014466608x401875
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective and attitude‐behaviour consistency in future‐oriented behaviours

Abstract: The authors propose that the salience of a distant-future time perspective, compared to a near-future time perspective, should increase attitude-behaviour and attitude-intention consistency for future-oriented behaviours. To test this prediction, time perspective was experimentally manipulated in three studies. Across studies, participants in the distant-future time perspective condition demonstrated a strong positive relationship between attitudes towards future-oriented behaviours (saving and environmental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 53 publications
(64 reference statements)
1
57
1
3
Order By: Relevance
“…We argued at the beginning of this paper that social change is likely to be predicated on the formation of new groups that can promote action in the present but are sustainable into the future also Jones & Morton, 2012;Rabinovich et al, 2010;Postmes et al, 2012). We also suggested that opinion-based group memberships are useful candidate groups in this regard McGarty, Lala & Thomas, 2012).…”
Section: Sustainable Collective Actionmentioning
confidence: 99%
“…We argued at the beginning of this paper that social change is likely to be predicated on the formation of new groups that can promote action in the present but are sustainable into the future also Jones & Morton, 2012;Rabinovich et al, 2010;Postmes et al, 2012). We also suggested that opinion-based group memberships are useful candidate groups in this regard McGarty, Lala & Thomas, 2012).…”
Section: Sustainable Collective Actionmentioning
confidence: 99%
“…A study on attitude-behaviour consistency showed that consistency increased if a distantfuture (long-term) time perspective was present as compared to only a near future (shortterm) time perspective for attitudes and behaviours regarding environmental protection and saving money (Rabinovich, Morton & Postmes, 2010). Another study on creative project teams found that teams with a relatively shorter time perspective focused more on the immediate present and task completion rather than on task elaboration compared to teams with a longer time perspective (Bakker, Boros, Kenis & Oerlemans, 2013).…”
Section: Length Of Collaboration Timementioning
confidence: 99%
“…In this respect, time perspective differs from the understanding of time in the social dilemma studies reviewed above where usually a single interaction (a so-called one-shot) vs. repeated interactions are compared within one laboratory session. Time perspective, in contrast, relates to the temporal aspects of collaborations and their impact on attitudes and behaviour and comes closest to the scope of this study about the effects of anticipated collaboration time.Previous studies found that time perspective can impact on decision-making and behaviour, for instance, that a future time perspective can help a person to "transcend 8[immediate] stimulus forces" (Zimbardo & Boyd, 1999, p. 1272, and to delay gratification.A study on attitude-behaviour consistency showed that consistency increased if a distantfuture (long-term) time perspective was present as compared to only a near future (shortterm) time perspective for attitudes and behaviours regarding environmental protection and saving money (Rabinovich, Morton & Postmes, 2010). Another study on creative project teams found that teams with a relatively shorter time perspective focused more on the immediate present and task completion rather than on task elaboration compared to teams with a longer time perspective (Bakker, Boros, Kenis & Oerlemans, 2013).…”
mentioning
confidence: 99%
“…The current study used few control variables particularly concerned with investors' demographic factors such as age, gender, experience, income and total investment as recommended by prior studies that demographic factors are better to be controlled (Norden, 2010;Milfont & Gouveia, 2006;Rabinovich, Morton, & Postmes, 2010). The main purpose of this study is to check the impact of financial literacy and behavioral biases influence on portfolio diversification while controlling investor's socio-demographic factor.…”
Section: Control Variablesmentioning
confidence: 99%